2001
DOI: 10.1021/ic0011009
|View full text |Cite
|
Sign up to set email alerts
|

Complex Magnetism and Magnetic Structures of the Metastable HoMnO3 Perovskite

Abstract: The magnetic properties and the low-temperature magnetic structures of the orthorhombic perovskite HoMnO3 (space group Pnma) have been studied on polycrystalline samples by magnetization, specific heat, and neutron diffraction measurements. By cooling, HoMnO3 exhibits three singularities at T N = 41 K, T ≈ 26 K, and T ≈ 6.5 K, suggesting a rich magnetic phase diagram. The neutron diffraction data show that below T N = 41 K, the Mn3+ magnetic moments become ordered in an antiferromagnetic arrangement, adopting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
211
2
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(233 citation statements)
references
References 36 publications
19
211
2
1
Order By: Relevance
“…29,34 Mncontaining DyMno 3 and HoMnO 3 show the same type of magnetic ordering but with doubling of unit cell along b-direction. 15,17 Expanding the same considerations on TMnO 3 , one can expect that strong J Mn−Tb prevents Tb of having regular τ Tb =1/2 b * structure presumably of G x A y -type (in one-dimensional case it would simply correspond to ↑↑↓↓).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…29,34 Mncontaining DyMno 3 and HoMnO 3 show the same type of magnetic ordering but with doubling of unit cell along b-direction. 15,17 Expanding the same considerations on TMnO 3 , one can expect that strong J Mn−Tb prevents Tb of having regular τ Tb =1/2 b * structure presumably of G x A y -type (in one-dimensional case it would simply correspond to ↑↑↓↓).…”
Section: Discussionmentioning
confidence: 90%
“…5,14 In some cases, they even contribute to the magnitude of the polarization as has been shown for DyMnO 3 . 3,15 A necessary condition for this is the ordering of rare earths with the same propagation vector as Mn, behavior confirmed now for RMnO 3 with R = Gd, Tb, Dy and Ho above their own ordering temperatures, T R N < 10 K. 8,16,17 Here, Mn-magnetic sublattice polarizes R-spins and the induced R-moment is defined by the strength of exchange interaction between Mn-and R-ions, J Mn−R .…”
Section: Introductionmentioning
confidence: 89%
“…The k s (∼0.295) at T N is incommensurate (IC) and decreases with decreasing T , and becomes nearly constant (k s =0.28) below ∼30 K. The anomalies in C/T and M at ∼27 K are in good agreement with the T where k s is locked at a constant value (T lock ). With further decreasing r R , Muñoz et al [7] reported that in polycrystalline HoMnO 3 (T N =41 K) the IC−to−commensurate (CM) magnetic phase transition takes place at ∼26 K, where the wave vector is (0, k s , 0) [0.4≤k s <0.5 (T -dependent) for the IC phase and k s = 1 2 for the CM one]. As displayed in Fig.…”
mentioning
confidence: 90%
“…Recently, a similar spin structure, i.e. the up-up-down-down order in a MnO 2 plane (E-type AF order in the Wollan-Koehler notation [6]), is found in a manganite, HoMnO 3 [7] with a significantly distorted perovskite structure. This has to be a bridge between the well-understood A-type AF in manganites and the unique magnetic ground state in nickelates.…”
mentioning
confidence: 99%
See 1 more Smart Citation